Simulasi Keracunan Bahan Kimia Berbasis Sekolah: Strategi Edukasi Penanganan Pertama - Nian Afrian Nuari; Damas Galuh Prayoga; Kharisma Maya Rini; Reviane Ayunda; Kusnul Kotimah; Revita Amaliya (PPNI UNIMMAN, 2024)
Poisoning by chemicals is a major public health issue that is frequently disregarded. Many people are yearly exposed to hazardous materials at home, at work, and when participating in outdoor activities. This exposure can happen by ingesting, skin contact, or inhalation. It can have a range of health effects, from minor ailments to serious illnesses. This community service project aims to implement a first aid education plan for chemical poisoning in schools using simulation techniques. The implementation method in this activity is a simulation, participants are taught practically how to handle poisoning situations, including recognizing symptoms, taking initial action, and knowing when to contact emergency services with a total of 25 partners from SMK Y Kediri Regency. The post-test findings indicated that participants' knowledge of chemical poisoning first aid had significantly increased. Most participants demonstrated a higher level of mastery of the necessary concepts and activities by answering nearly all questions correctly. Students that participate in this program get practical skills in addition to information. It is anticipated that this will lessen the possibility and effects of chemical poisoning while also enhancing community preparedness for emergencies.